Ultra-Early Differential Diagnosis of Acute Cerebral Ischemia and Hemorrhagic Stroke by Measuring the Prehospital Release Rate of GFAP. (12th August 2021) - Mattila, Olli S; Ashton, Nicholas J; Blennow, Kaj; Zetterberg, Henrik; Harve-Rytsälä, Heini; Pihlasviita, Saana; Ritvonen, Juhani; Sibolt, Gerli; Nukarinen, Tiina; Curtze, Sami; Strbian, Daniel; Pystynen, Mikko; et al.
Abstract: Background: Plasma glial fibrillary acidic protein (GFAP) and tau are promising markers for differentiating acute cerebral ischemia (ACI) and hemorrhagic stroke (HS), but their prehospital dynamics and usefulness are unknown. Methods: We performed ultra-sensitivite single-molecule array (Simoa ® ) measurements of plasma GFAP and total tau in a stroke code patient cohort with cardinal stroke symptoms [National Institutes of Health Stroke Scale (NIHSS) ≥3]. Sequential sampling included 2 ultra-early samples, and a follow-up sample on the next morning. Results: We included 272 cases (203 ACI, 60 HS, and 9 stroke mimics). Median (IQR) last-known-well to sampling time was 53 (35–90) minutes for initial prehospital samples, 90 (67–130) minutes for secondary acute samples, and 21 (16–24) hours for next morning samples. Plasma GFAP was significantly higher in patients with HS than ACI ( P  < 0.001 for <1 hour and <3 hour prehospital samples, and <3 hour secondary samples), while total tau showed no intergroup difference. The prehospital GFAP release rate (pg/mL/minute) occurring between the 2 very early samples was significantly higher in patients with HS than ACI [2.4 (0.6–14.1)] versus 0.3 (−0.3–0.9) pg/mL/minute, P  < 0.001. For cases with <3 hour prehospital sampling (ACI n  = 178, HS n  = 59), a combined rule (prehospital GFAP >410 pg/mL, or prehospital GFAP 90–410 pg/mL together with GFAP release >0.6 pg/mL/minute) enabled ruling out HS with high certainty (NPV 98.4%) in 68% of patients with ACI (sensitivity for HS 96.6%, specificity 68%, PPV 50%). Conclusions: In comparison to single-point measurement, monitoring the prehospital GFAP release rate improves ultra-early differentiation of stroke subtypes. With serial measurement GFAP has potential to improve future prehospital stroke diagnostics.